Sheet Flow Effects on Sediment Transport in a Degraded Ridge‐and‐Slough Wetland: Insights Using Molecular Markers. Issue 10 (8th October 2018) - Regier, Peter; He, Ding; Saunders, Colin J.; Jara, Blanca; Hansen, Chris; Newman, Sue; Tate‐Boldt, Erik; Coronado‐Molina, Carlos; Jaffé, Rudolf
Abstract: Wetland ecosystems are often characterized by self‐organized landscape patterning, driven by abiotic and biotic factors. In the Florida Everglades, natural sheet flow is hypothesized to have distributed sediments to form the pattern of linear emergent ridges and submerged sloughs. Drainage and barriers to flow have degraded these microtopographic features. As part of the Comprehensive Everglades Restoration Plan, the Decompartmentalization Physical Model is a landscape‐scale experiment to evaluate ecosystem responses to restored sheet flow by increasing freshwater inputs and removing barriers to flow. To test the proposed mechanism that flow rebuilds ridge‐slough microtopography by remobilizing slough sediments into ridges, four molecular markers capable of distinguishing ridge, slough, and microbial sources were evaluated in flocculent benthic sediments ( floc ) and advected sediments (collected in traps) during preflow, high‐flow, and postflow conditions over 4 years. The combined use of the four biomarkers, namely, the aquatic proxy (Paq), C20 highly branched isoprenoids, kaurenes, and botryococcenes, showed compositional patterns that clearly distinguished ridge and slough organic matter. Of these molecular parameters, the Paq was the most reliable in distinguishing among organic matter sources. Long‐term patterns in floc Paq at ridge and slough sites indicate a general increase, indicative of preferential mobilization of slough material. The Paq values for advected sediments are also strongly associated with slough environments, supporting temporal trends in floc samples. Our results tentatively confirm the hypothesis that increased flow in degraded ridge‐and‐slough wetlands, and associated sediment transport, is a potentially viable mechanism to restore historic patterns of microtopography. Plain Language Summary: We examined how experimental flows within the Decompartmentalization Physical Model (DPM) altered the movement of benthic sediment (floc) in ridge and slough habitats, an important mechanism for restoring pattern and topography of the historic Everglades ridge‐and‐slough landscape. The approach is novel in utilizing molecular organic biomarkers that identify sources of organic matter from ridges and sloughs to infer the movement of floc. Results so far are promising in suggesting that sediment redistribution does occur and may over longer time periods help rebuild topography, an important objective of large‐scale flow restoration projects such as those proposed in the Comprehensive Everglades Restoration Plan (CERP). Key Points: The aquatic proxy (Paq) was used to distinguish organic matter sources of sediments from Everglades ridge‐and‐slough habitats Temporal changes in Paq showed preferential mobilization of slough material and movement into ridges Sheet flow redistributes sediment, an important step in restoring historic landscape pattern and microtopography